INCIVILITY IN DIGITAL ERA: A STUDY ON CYBERBULLYING - (:unkn) unknown (FUTURE ACAD, 2019)
Cyberbullying, the intense inappropriate and hostile behaviors online, represents the dark side of digital era we are living in. The increased frequency of this cyberincivility among both youth and adults and the negative psychological and organizational impacts it has on victims have made it interesting topic for researchers. The aim of this study was to investigate the positive attitudes toward cyberbullying and its facilitators, anonymity, strength differential and being a victim of cyberincivility. The research was conducted on 481 higher education students (53.4% females and 46.2% males; 56.8% working and 43.2% without any work experience). Results revealed that when one perceives that there is a difference in strength (either physical or in terms of status), he/she might be more inclined to develop attitudes for kidding or taking revenge for the past behaviors he had encountered in the past. In addition, being humiliated is found to increase the positive attitude toward kidding and being ignored in cyber environment is found to increase the positive attitude toward fit for tat. With respect to gender, males had higher positive attitude toward kidding than females. Males with no work experience are found to perceive anonymity more than males with experience and females with work experience perceived anonymity more than females with no work experience. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Anonymity; cyberbullying; cyberincivility; strength differential; victimization; CYBER INCIVILITY; PERPETRATION; WORKPLACE; WORK; PREVALENCE; PREDICTORS; BEHAVIOR; TARGETS; IMPACT; ONLINE